Myanmar Economic Monitor, December 2019 : Resilience Amidst Risk - World Bank (World Bank, Washington, DC, 2020)
Myanmar’s economy continues to show resilience despite the global slowdown and domestic uncertainties. Its economy is estimated to have grown at 6.3 percent in 2018/191, marginally higher than 6.2 percent in 2017/18, supported by better performance in the manufacturing and services sectors. Macroeconomic volatility has increased since the June 2019 Myanmar Economic Monitor, with inflation reaching double digits in July 2019. Economic growth is expected to reach 6.4 percent in 2019/20, helped by growing investment in the transport and telecommunication sectors and government’s planned infrastructure spending before the 2020 elections. Risks to the economic outlook are tilted to the downside due to slowing global and regional growth, and continued uncertainty about investor perceptions triggered by the Rakhine crisis and the pace of reforms prior to the 2020 general elections, although the pace has thus far been strong.